Is this normal? The cost of assuming that derivatives have normal returns - Radoslav Raykov (Bank of Canada, 2024)
Derivatives exchanges often determine collateral requirements, which are fundamental to market safety, with dated risk models assuming normal returns. However, derivatives returns are heavy-tailed, which leads to the systematic under-collection of collateral (margin). This paper uses extreme value theory (EVT) to evaluate the cost of this margin inadequacy to market participants in the event of default. I find that the Canadian futures market was under-margined by about 1.6 billion during the Great Financial Crisis, and that the default of the highest-impact participant generates a cost of up to 302 million to be absorbed by surviving participants. I show that this cost can consume the market's entire default fund and result in costly risk mutualization. I advocate for the adoption of EVT as a benchmarking tool and argue that the regulation of exchanges should be revised for financial products with heavy tails.
Keywords: G10; G11; G20; 330; Financial institutions; Financial stability